(untitled) (Prithvi Journal of Research and Innovation, 2023)
The aim of the present study is to investigate the position and impact of four dimensions of academic sectors: work autonomy, cooperation and relations, adequate and fair benefit, and work atmosphere on the quality of work-life (QWL) of university teachers. To address this objective, the study is descriptive and explanatory. The information was composed of permanent faculty members employed on nominated campuses by applying a stratified sampling technique. A Google Form-structured questionnaire was applied to collect the data. To collect the data, 301 questionnaires were disseminated, and among them, 220 responses were found to be valid and applicable to the study. Empirical analysis was done using SPSS, and descriptive statistics were conducted by applying the mean and standard deviation. Impact of four dimensions of QWL was examined by employing multiple regression analysis. The findings of the study showed that the work environment, relations and cooperation, and fair and adequate compensation aspects of QWL amongst faculties positively and significantly impacted on the QWL; however, the autonomy of the work had an insignificant effect on the QWL. This study is expected to assist as valued input for the academies in recognizing the vital issues of place of work, advance schemes to discourse, and increase the value of employed situations.